Crystal structure of N-ethyl-2-(1,2,3,4-tetrahydronaphthalen-1-ylidene)hydrazinecarbothioamide - De Oliveira, Adriano Bof; Beck, Johannes; Landvogt, Christian; De Farias, Renan Lira [UNESP]; Feitoza, Bárbara Regina Santos (International Union of Crystallography (IUCr), 2017)
There are two crystallographically independent molecules in the asymmetric unit of the title compound, C13H17N3S, one of them being disordered over the methyl group [site-occupancy ratio = 0.705(5):0.295(5)]. The maximum r.m.s. deviations from the mean plane of the non-H atoms for the tetralone fragments amount to 0.4572(17) and 0.4558(15)Å. The N - N - C - N fragments are not planar and torsion angles are -9.4(2) and 8.3(2)°. In the crystal, the molecules are linked by weak N - H⋯S interactions into chains along [100] with graph-set motif C(4) and connected by weak N - H⋯S and C - H⋯S interactions, forming R2 1(10) rings. The Hirshfeld surface analysis indicates that the most important contributions for the crystal packing are the H⋯H (64.20%), H⋯S (12.60%) and H⋯C (12.00%) interactions. The crystal packing resembles a herringbone arrangement when viewed along [001].
Keywords: crystal structure; Hirshfeld surface calculation; tetralone thiosemicarbazone derivative